Postnatal support for mothers living in disadvantaged inner city areas: a randomised controlled trial. Issue 4 (14th March 2005) - Wiggins, M; Oakley, A; Roberts, I; Turner, H; Rajan, L; Austerberry, H; Mujica, R; Mugford, M; Barker, M
Abstract : Study objective: To evaluate the effect of two forms of postnatal social support for disadvantaged inner city mothers on maternal and child health outcomes. Design: Randomised controlled trial with economic and process evaluations and follow up at 12 and 18 months. The two intervention groups received either the offer of a year of monthly supportive listening home visits by a support health visitor (SHV), or a year of support from community groups providing drop in sessions, home visiting and/or telephone support (CGS). Each was compared with a control group that received standard health visitor services. Setting: Two disadvantaged boroughs of London, United Kingdom. Participants: 731 women from culturally diverse backgrounds with infants. Main results: At 12 and 18 months, there was little impact for either intervention on the main outcomes: child injury (SHV: relative risk 0.99; 95% confidence intervals 0.68 to 1.45, CGS: 0.91; 0.61 to1.36), maternal smoking (SHV: 0.86; 0.62 to 1.19, CGS: 0.97; 0.72 to 1.33) or maternal depression (SHV: 0.86; 0.62 to1.19, CGS: 0.93; 0.69 to 1.27). SHV women had different patterns of health service use (with fewer taking their children to the GP) and had less anxious experiences of motherhood than control women. User satisfaction with the SHV intervention was high. Uptake of the CGS intervention was low: 19%, compared with 94% for the SHV intervention. Conclusions: There was no evidence of impact on the primary outcomes of either intervention among this culturally diverse population. The SHV intervention was associated with improvement in some of the secondary outcomes.